Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert Tote; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Linguistic Minorites and Society, 2013)
Résumé La tendance actuelle montre que les institutions des services de santé et les gouvernements répondent de façon inadéquate aux besoins de plus en plus nombreux d’accès aux services de santé par les populations vieillissantes du Canada et d’autres pays développés. Après l’analyse de l’enquête post-censitaire 2006 de Statistiques Canada sur la Vitalité des Minorités de Langue Officielle, cette étude démontre qu’outre l’age, et en plus d’autres déterminants, les barrières linguistiques auxquelles font face les aînés de langue officielle en situation minoritaire affectent davantage l’autoévaluation de leur santé. Cette étude suggère quelques pistes de solution dont la compréhension des réalités contextuelles, l’amélioration de l’environnement linguistique et des services de santé dans la langue minoritaire. Mots-clés : déterminants de la santé, statut minoritaire, santé perçue, minorités linguistiques, aînés Abstract Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language. Keywords: health determinants, minority status, self-rated health, linguistic minorities, older adults

Soins à domicile en français. Rapport final - Atlantic Evaluation Group Inc (2013)

Diverging socioeconomic inequality in life expectancy of Francophones and Anglophones in Montréal, Québec: Tobacco to blame? - Auger, Nathalie; Harper, Sam; Barry, Amadou D. (Journal of Public Health: From Theory to Practice, 2013)
Aim We evaluated the ages and causes of death contributing to life expectancy gaps between economically advantaged and disadvantaged Francophones and Anglophones of Montréal, a Canadian metropolitan centre. Subject and Methods We partitioned the life expectancy gap at birth between socioeconomically disadvantaged and advantaged Francophones and Anglophones of Montréal (Québec) into age and cause of death components for two periods (1989–1993, 2002–2006). Changes in the contributions of causes over time were evaluated. Results Life expectancy was lower for disadvantaged Francophones and Anglophones by 5 years in men and 1.6 years in women compared with advantaged individuals. Over time, the socioeconomic gap widened for Francophones (men 0.3 years, women 2.8 years), due to smaller reductions in mortality from tobacco-related causes (cardiovascular, cancer, respiratory) in disadvantaged than in advantaged Francophones, especially after age ≥65 years (except lung cancer mortality that increased, particularly in disadvantaged women). The socioeconomic gap narrowed, however, for Anglophones (men 1.0 year, women 0.6 years), due to greater reductions in cardiovascular mortality in disadvantaged than advantaged Anglophones. Conclusion Socioeconomic inequalities in life expectancy decreased for Anglophones but increased for Francophones in Montréal due to underlying trends in tobacco-related mortality. Despite strong tobacco control laws in Canada, socioeconomic inequality in tobacco-related mortality is widening for Francophones in Montréal.

Contribution of local area deprivation to cultural-linguistic inequalities in foetal growth restriction: Trends over time in a Canadian metropolitan centre - Auger, Nathalie; Park, Alison L.; Daniel, Mark (Health & Place, 2013)
This study investigated temporal trends in heterogeneity of foetal growth restriction across neighbourhood deprivation levels for two culturally distinct communities (Anglophones and Francophones) in a North American metropolitan centre. Inequalities in foetal growth restriction related to deprivation fell from 1989 to 2008 for Francophones, but initial improvements for Anglophones later reversed with a rise in poor foetal growth in the most materially disadvantaged and, unexpectedly, advantaged areas as well. Inequalities in foetal growth restriction related to neighbourhood material deprivation may be emerging in this minority Anglophone population. Potential mechanisms underlying these trends are discussed, as well as implications for perinatal health policy.

Comparison of dietary intake between Francophones and Anglophones in Canada: Data from CCHS2.2 - Batal, Malek; Makvandi, Ewa; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective To compare the dietary intake and food choices between Francophone Canadians in a state of linguistic minority (outside of Quebec) and the English-speaking majority. Methods We used the 2004 Canadian Community Health Survey (CCHS) cycle 2.2 (general health and 24-hour dietary recalls) to describe dietary intake of Francophone Canadians (excluding Quebec) and compare them to the English-speaking majority. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. The mean differences in daily nutrient and food intake were assessed by t and chi-square tests. Results Differences in total energy and daily food intakes by language groups were not observed in the sample; however, significant differences in weekly consumption were found in different age and sex categories: lower fruits and vegetables consumption, and vitamins and macronutrients intakes for older Francophone men and higher intakes of energy and saturated fat from “unhealthy” foods for Francophone men 19–30 years of age. Based on the Acceptable Macronutrients Distribution Range (AMDR), approximately 50% of the sample exceeded their acceptable energy intake from saturated fats, and 80% were below their required intake of linoleic fatty acid. Conclusion We confirmed that belonging to Francophone minorities in Canada affects food choices and nutritional well-being of this population. The most vulnerable groups identified by our study were Francophone men in the youngest (19-30) and older (50 and over) age categories. The extent to which the cultural setting influences the diet and, in turn, the health of the minority population needs further examination.

La vulnérabilité de femmes monoparentales francophones à risque de sans-abrisme dans une communauté du Nord de l’Ontario - Benoit, Monique; Lavoie, Anne Marise; Muray, Kalum; Watson, Shelley; Beaudoin, Monique (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif Cette étude avait pour but d’examiner l’état de vulnérabilité de femmes monoparentales à risque de sans-abrisme dans une minorité francophone du Nord de l’Ontario. Le projet visait plus largement à documenter la quête d’autonomie de ces femmes dans ce contexte précis. Méthode L’étude reposait sur une approche qualitative fondée sur onze récits de vie obtenus auprès de cinq femmes. Bien qu’aucune femme n’était sans-abri (soit dans la rue) lors des entrevues, deux étaient sans domicile fixe (en état d’itinérance) et les autres étaient à risque. Elles étaient âgées de 20 à 59 ans, ayant complété en majorité une 12e année de scolarité. Résultats L’état de vulnérabilité représenté à travers les trajectoires de vie a été analysé en tenant compte de leur situation économique, sociale, leur état de santé et les ressources culturelles de chacune des femmes interrogées. Conclusion La trajectoire de vie de ces femmes nous a fait comprendre que leur grande vulnérabilité s’inscrit dans un espace d’autonomie relative à ce que les organismes d’aide parviennent à offrir, en terme de services, en contexte linguistique minoritaire. Aussi, la triple stigmatisation à la fois économique, linguistique et fondée sur des rapports de genre exigerait une réflexion plus large sur la résilience de ces femmes dans le passage de la pauvreté (économique) à l’exclusion sociale (et linguistique), puis à la vulnérabilité. Enfin, chacun des thèmes abordés dans cette étude nous a montré la résilience de ces femmes résistantes à la vulnérabilité et chez qui la quête d’autonomie est une lutte constante.

Inventaires des services de santé en français dans l’Ouest canadien : entre improvisation et gouvernance : 2000‐2010 - Boily, Frédéric; Gagné, Learry (Revue Gouvernance, 2013)
La difficulté pour les communautés francophones en situation minoritaire au Canada d’obtenir des services de santé dans leur langue est bien connue. Le problème est encore plus criant dans l’Ouest canadien, défavorisé par une faiblesse démographique et une grande dispersion de la population par rapport à l’Est (surtout l’Ontario et le Nouveau-Brunswick). Dans ce contexte, la mobilisation des francophones pour la défense de leurs intérêts est essentielle. Ce projet porte sur les relations entre les gouvernements provinciaux de l’Ouest, le gouvernement fédéral et les groupes francophones minoritaires en matière de politique de santé. Nous proposons de nous concentrer sur les provinces de la Colombie-Britannique, de l’Alberta et de la Saskatchewan pour la période récente allant de 2000 à 2010. L’analyse porte principalement sur les facteurs en politique publique qui ont permis à ces groupes de revendiquer un certain nombre de services de santé. Nous établissons une relation entre la participation active du fédéral durant cette période, la participation plutôt passive des provinces, et la préférence pour les projets de santé publique où le fédéral a pu jouer un rôle sans empiéter sur les pouvoirs provinciaux.

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Language as an important determinant of poverty in the aging Francophone minority population in Canada - Bouchard, Louise; Sedigh, Golnaz; Batal, Malek; Imbeault, Pascal; Makvandi, Ewa; Sylva de la Vega, E. (The International Journal of Aging and Society, 2013)
Six cycles of the Canadian Community Health surveys (CCHS) from 2001 to 2009 were used to compare the income and health of the minority French-speaking aging population (over 65 years of age) to the majority English-speaking group in Canada, excluding Quebec. A sequential multivariate logistic regression analysis showed that men and women of the minority French-speaking population of this age group, living in Canada outside the province of Quebec, are more likely to be in the poorest income quintile than their English-speaking counterparts. This disparity remains significant even after controlling for residence (province and urban/rural), household makeup (living alone or not), immigration status, education, employment, health status, chronic diseases, and restrictions in activities. Independently of other key socio-demographic factors modulating health, our results also show that being in the poorest income quintile is associated with a poor self-perceived health, a finding that was more prevalent in the French-speaking aging population living in situation of minority.

Suicide mortality gap between Francophones and Anglophones of Quebec, Canada - Burrows, Stephanie; Auger, Nathalie; Tamambang, Lum; Barry, Amadou. D. (Social psychiatry and psychiatric epidemiology, 2013)
Purpose Few studies evaluate language-group differences in suicide mortality. This study assessed the suicide mortality gap between Francophones and Anglophones of Quebec, Canada according to age, sex, method, region and socioeconomic deprivation. Methods Suicide decedents were extracted from the Quebec death file for 1989–2007 (N = 24,465). Age- and sex-specific suicide mortality rates were calculated for four periods (1989–1993, 1994–1998, 1999–2003, 2004–2007) for Francophones and Anglophones aged ≥10 years. Age-standardized rates of suicide by method, region, and level of social and material deprivation were calculated for each sex. Rate ratios and rate differences were estimated. Results Suicide rates for Francophones were two to three times higher than rates for Anglophones, and differences were greatest for adults aged 25–64 years. Francophone males had more than two times the rate of suicide by hanging or firearms than Anglophone males. Francophone females had twice the rate of hanging, poisoning or firearm suicide as Anglophone females, although precision was low. Francophone-Anglophone suicide mortality gaps were higher in urban areas despite lower suicide rates, and varied little across levels of social and material deprivation. Conclusions There was a large suicide mortality gap between Francophones and Anglophones of Quebec; especially, among adults aged 25–64 years.

Bien vieillir dans sa langue, sa culture et sa communauté. Soutien d’institutions fédérales clés et portrait des aînés anglophones du Québec - Commissariat aux langues officielles (Gouvernement du Canada, 2013)

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Le surplus de poids chez les francophones et les anglophones - Gagnon-Arpin, Isabelle; Makvandi, Ewa; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs Des études récentes rapportent une prévalence d’embonpoint et d’obésité plus élevée chez les francophones en situation linguistique minoritaire en comparaison à la majorité anglophone du Canada. L’objectif de l’étude est de vérifier si l’appartenance au groupe linguistique minoritaire s’ajoute aux déterminants sociaux du surplus de poids. Méthode Les statistiques descriptives (n=128 986), provenant de cinq cycles de l’Enquête sur la santé dans les collectivités canadiennes, ont été croisées en fonction de la langue et du sexe des individus. Deux modèles de régression logistique multivariée, pour les hommes et pour les femmes, ont permis de tester l’association entre le surplus de poids et la langue en contrôlant pour les déterminants socioéconomiques et comportementaux. Résultats La prévalence du surplus de poids est plus élevée chez les francophones que chez les anglophones de l’Ontario, bien que cette différence ne soit plus significative lorsque le modèle est ajusté pour les caractéristiques socioéconomiques et comportementales. Néanmoins, les francophones sont plus âgés, moins éduqués et vivent davantage en milieu rural que leurs homologues anglophones, un contexte qui les rend plus vulnérables. Conclusion L’étude vient réaffirmer le rôle des déterminants sociaux et comportementaux dans la prévalence du surplus de poids. Bien que la langue n’influence pas directement le surplus de poids, compte tenu de la réalité socioéconomique de la minorité francophone, représentée en plus grande proportion dans les strates de la population plus vulnérable au surplus de poids, l’appartenance à un groupe minoritaire devrait interpeller les planificateurs de la santé.

Les services de santé en français pour les communautés francophones et acadiennes en situation minoritaire du Canada : bonification du schéma du CCCFSM (2001) - Giguère, Louis (Nouvelles perspectives en sciences sociales, 2013)
Nous bonifions le schéma du CCCFSM (2001) sur le développement des services de santé en français pour les communautés francophones et acadiennes en situation minoritaire (CFASM) du Canada à l’aide de données probantes recueillies lors du recensement national de 2006. Notre approche consiste à choisir, à partir d’une procédure statistique, une mesure de masse critique de francophones qui met en évidence un schème cohérent d’offre et de demande de services de santé sur une base géographique juridictionnelle. L’offre et la demande sont plus grandes là où la vitalité linguistique des CFASM est plus grande. Dans l’ensemble, l’offre tombe en deçà de la demande; ceci suggère une demande latente de services en français et est consistant avec les études d’offre active des services en français dans les CFASM. Nos résultats sont aussi consistants avec les trois phases évolutives de sensibilisation, de structuration et de consolidation proposées par le CCCFSM (2001). Nous discutons des limitations méthodologiques et en tirons des leçons pour les réseaux de santé francophones des CFASM. Mots-clés : CFASM, CLOSM, communauté francophone, minoritaire, vitalité linguistique, langues officielles, réseaux de santé, services en français, offre et demande

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549 -X) - Lafrenière, Sylvie (Statistique Canada, 2013)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.

Lifestyle habits and health indicators of Québec Anglophones - Lussier, Marie-Hélène; Trempe, Normand (Institut national de santé publique du Québec, 2013)

Quelques habitudes de vie et indicateurs de santé des anglophones du Québec - Lussier, Marie-Hélène; Trempe, Normand (Institut national de santé publique du Québec, 2013)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Enjoying your senior years in your own language, culture and community. Federal support from key institutions and a portrait of English-speaking seniors in Quebec - Office of the commissioner of official languages (Federal support from key institutions and a portrait of English-speaking seniors in Quebec, 2013)

Adaptation linguistique des soins et des services de santé : enjeux et stratégies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Language adaptation in health care and health services: Issues and strategies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Les professionnels de la santé et des services sociaux intervenant auprès des francophones minoritaires : l’enjeu du capital social - Savard, Sébastien; Arcand, Isabelle; Drolet, Marie; Benoît, Josée; Savard, Jacinthe; Lagacé, Josée (Francophonies d’Amérique, 2013)
Cet article présente les résultats d’une recherche qualitative sur la collaboration et le partenariat entre les professionnels des services sociaux et de la santé qui interviennent auprès de francophones vivant en situation minoritaire en Ontario. L’étude met en lumière, à partir de l’information recueillie auprès de 43 professionnels rencontrés dans huit groupes de discussion, le contexte qui caractérise leur pratique, les défis qu’ils rencontrent dans leur tentative de créer des liens de collaboration avec d’autres professionnels qui oeuvrent auprès des communautés francophones minoritaires ainsi que les facteurs qui facilitent l’établissement de partenariats entre les différents intervenants qui répondent aux besoins de cette population. Les résultats font ressortir que le sentiment d’appartenance, la confiance et l’engagement des professionnels envers la communauté francophone, de même que les valeurs de réciprocité et de solidarité qui les habitent sont des éléments qui favorisent le développement du capital social de la communauté des intervenants. Cependant, le manque de mécanismes permettant la consolidation et la pérennisation des relations de collaboration constitue un facteur qui limite la capacité de bonifier le capital social des professionnels de la santé et des services sociaux francophones et bilingues.

Potential for patient-physician language discordance in Ontario - Sears, Jennifer; Khan, Kamran; Ardern, Chris . I.; Tamim, Hala (BMC Health Services Research, 2013)
Background Patient-Physician language discordance occurs when the patient and physician lack proficiency in the same language(s). Previous literature suggests language discordant clinical encounters compromise patient quality of care and health outcomes. The objective of this study was to quantify and visualize the linguistic and spatial mismatch between Ontario’s population not proficient in English or French but proficient in one of the top five non-official languages and the physicians who are proficient in the same non-official language. Methods Using data from the 2006 Canadian census and the 2006 Canadian Medical Directory, we determined the number of non-English/non-French (NENF) speaking individuals and the number of Ontario physicians proficient in the top five non-official languages in each census division (CD) of Ontario. For each non-official language, we produced bi-variate choropleth maps of Ontario, broken down into the 49 CDs, to determine which CDs had the highest risk of language discordant clinical encounters. Results According to the 2006 Canadian census, the top five non-official languages spoken by Ontario’s NENF population were: Chinese, Italian, Punjabi, Portuguese and Spanish. For each of the top five non-official languages, there were at least 5 census divisions with a NENF population speaking a non-official language without any primary care physicians proficient in that non-official language. The size of NENF populations within these CDs ranged from 10 individuals to 1,470 individuals. Conclusions Understanding the linguistic capabilities of Ontario’s immigrant population & the linguistic capabilities of Ontario’s primary care physicians is essential to ensure equal access and quality of healthcare. As immigration continues to increase, we may find that the linguistic needs of Ontario’s immigrant population diverge from the linguistic capabilities of Ontario’s primary care physicians. Further research on the language discordance in Ontario is needed in order to reduce the risk of language discordant clinical encounters and the negative health outcomes associated with these encounters.

Avoidable mortality of the two main linguistic communities in Québec. Language as a determinant of health status and service quality - Trempe, Normand; Diogo Barry, Amadou D.; Lussier, Marie-Hélène.; Lo, Ernest (Institut national de santé publique du Québec, 2013)

La mortalité évitable des deux principales communautés linguistiques du Québec. La langue, déterminant de l'état de santé et la qualité des services - Trempe, Normand; Diogo Barry, Amadou; Lussier, Marie-Hélène; Lo, Ernest (Institut national de santé publique du Québec, 2013)

Dépistage nutritionnel chez les aînés en établissements de soins de santé : comparaison entre les établissements francophones et anglophones - Villalon, Lita; Laporte, Manon; Carrier, Natalie (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs La malnutrition des aînés est un problème répandu dans les hôpitaux et les foyers de soins. Cependant, la pratique du dépistage nutritionnel dans ces milieux est peu connue, particulièrement dans les établissements francophones de soins de santé. Cette étude avait pour objectifs de comparer la situation du dépistage nutritionnel des aînés dans les établissements de soins de santé francophones et anglophones du Nouveau-Brunswick, ainsi que les perceptions et les pratiques des professionnels de la santé. Méthodes Les données sur les paramètres de dépistage ont été puisées directement dans les dossiers médicaux des patients/résidents âgés. Les perceptions et les pratiques de dépistage nutritionnel des professionnels de la santé (médecins, infirmiers, diététistes) ont été recueillies au moyen de questionnaires. Résultats Cinq hôpitaux et 31 foyers de soins de longue durée du Nouveau-Brunswick ainsi que 421 patients/résidents et 457 professionnels de la santé ont participé à l’étude. Des différences significatives quant à la disponibilité des paramètres de dépistage furent observées entre les patients/résidents francophones et anglophones; les francophones bénéficiant moins de certains paramètres de dépistage dont le poids à l’admission, la perte d’appétit et la fraction des repas consommés. Les perceptions des professionnels quant au dépistage nutritionnel varient selon la profession et la langue de l’établissement. Plusieurs obstacles au dépistage nutritionnel sont relevés. Conclusion La disponibilité moindre de paramètres de dépistage dans les milieux francophones et la sous-évaluation de la malnutrition par les médecins et les infirmiers sont des barrières pouvant influencer le dépistage nutritionnel en établissements de soins de santé francophones.